Micromolar affinity CAR T cells to ICAM-1 achieves rapid tumor elimination while avoiding systemic toxicity. Issue 1 (December 2017) - Park, Spencer; Shevlin, Enda; Vedvyas, Yogindra; Zaman, Marjan; Park, Susan; Hsu, Yen-Michael; Min, Irene; Jin, Moonsoo
Abstract Adoptive transfer of high-affinity chimeric antigen receptor (CAR) T cells targeting hematological cancers has yielded impressive clinical results. However, safety concerns regarding target expression on healthy tissue and poor efficacy have hampered application to solid tumors. Here, a panel of affinity-variant CARs were constructed targeting overexpressed ICAM-1, a broad tumor biomarker, using its physiological ligand, LFA-1. Anti-tumor T cell potencyin vitro was directly proportional to CAR affinity and ICAM-1 density. In a solid tumor mouse model allowing simultaneous monitoring of anti-tumor potency and systemic off-tumor toxicity, micromolar affinity CAR T cells demonstrated superior anti-tumor efficacy and safety compared to their nanomolar counterparts. Longitudinal T cell tracking by PET/CT and concurrent cytokine measurement revealed superior expansion and contraction kinetics of micromolar affinity CAR T cells. Therefore, we developed an ICAM-1 specific CAR with broad anti-tumor applicability that utilized a reduced affinity targeting strategy to significantly boost efficacy and safety.